Competition Law in Malaysia - Nasarudin Abdul Rahman, (Thomson Reuters Asia, 2021)
Competition law is developing dynamically in Malaysia. This book provides a useful analysis and explanation of the regulatory scheme, discussing the various powers and functions of the competition regulator as well as the enforcement and procedural aspects of Malaysian competition law. The second edition of this book discusses the more recent developments surrounding the Competition Act 2010 as well as the competition regime under various sectoral regulations.